2010
DOI: 10.1126/science.1196284
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase Gene Mutations in Familial Acne Inversa

Abstract: Acne inversa (AI), also known as hidradenitis suppurativa, is a chronic, recurrent, inflammatory disease of hair follicles that often runs in families. We studied six Chinese families with features of AI as well as additional skin lesions on back, face, nape, and waist and found independent loss-of-function mutations in PSENEN, PSEN1, or NCSTN, the genes encoding essential components of the γ-secretase multiprotein complex. Our results identify the γ-secretase component genes as the culprits for a subset of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
356
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(382 citation statements)
references
References 7 publications
9
356
0
8
Order By: Relevance
“…This unique role may be caused by γ-secretase-independent activities of PS that are more relevant to AD pathogenesis, by a higher intrinsic mutation rate of the human PSEN genes than of the other γ-secretase subunit genes, or by PS forming the catalytic core of the γ-secretase complex. Interestingly, recent human genetic studies identified large numbers of loss-of-function mutations in the Nct (17) and Pen-2 (3) genes that are associated with familial acne inversa or hidradenitis suppurativa (27)(28)(29)(30)(31). The lack of mutations identified in the Aph-1A and Aph-1B genes may reflect the genetic redundancy of the Aph-1 family; however, one mutation was reported in the PSEN1 gene despite the presence of its family member PSEN2 (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique role may be caused by γ-secretase-independent activities of PS that are more relevant to AD pathogenesis, by a higher intrinsic mutation rate of the human PSEN genes than of the other γ-secretase subunit genes, or by PS forming the catalytic core of the γ-secretase complex. Interestingly, recent human genetic studies identified large numbers of loss-of-function mutations in the Nct (17) and Pen-2 (3) genes that are associated with familial acne inversa or hidradenitis suppurativa (27)(28)(29)(30)(31). The lack of mutations identified in the Aph-1A and Aph-1B genes may reflect the genetic redundancy of the Aph-1 family; however, one mutation was reported in the PSEN1 gene despite the presence of its family member PSEN2 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent human genetic studies identified large numbers of loss-of-function mutations in the Nct (17) and Pen-2 (3) genes that are associated with familial acne inversa or hidradenitis suppurativa (27)(28)(29)(30)(31). The lack of mutations identified in the Aph-1A and Aph-1B genes may reflect the genetic redundancy of the Aph-1 family; however, one mutation was reported in the PSEN1 gene despite the presence of its family member PSEN2 (27). Because the identified mutations are mostly dominantly inherited loss-offunction mutations (nonsense or frame-shift), these findings indicate that partial loss of γ-secretase activity because of haploinsufficiency of these genes leads to acne inversa.…”
Section: Discussionmentioning
confidence: 99%
“…1C), does not follow the "fAD mutation reading frame preservation rule" since it causes a frameshift in exon 7 and truncation of the open reading frame. This mutation does not appear to cause fAD [89].…”
Section: Changes In the Non-␥-secretase Activity(ies) Of Psen Underlimentioning
confidence: 82%
“…Remarkably, these have never been found but mutations in PSEN1, NCSTN, and PSENEN have been found in another disease, inherited acne inversa [89] (also known as hidradenitis suppurativa). It is also very significant that the single known mutation in PSEN1 causing acne inversa, P242LfsX11 (Fig.…”
Section: Changes In the Non-␥-secretase Activity(ies) Of Psen Underlimentioning
confidence: 99%
“…A szövet-tani minták elemzésének másik szembetűnő lelete az acné-ből jól ismert follicularis hiperkeratinizáció/okklúzió volt, mely a folliculusok kitágulásához majd roncsolódásához vezet, így a baktériumokban gazdag törmelék a dermist infiltrálva annak gyulladását eredményezi felvetve, hogy a baktériumok és a különböző gyulladásos útvonalak éppúgy fontosak lehetnek ebben a betegségben is (1. ábra). A gyulladásban szerepet játszó sejteken az acnéban ismerthez hasonlóan, szintén fokozottan vannak jelen a Toll-like receptorok (TLR) (3), illetve a legfrissebb teljes szöveti mintákon elvégzett génexpressziós analízisek a TNF-α, IL-1 és a NOD-like receptor (NLRP) gének/útvonalak fokozott kifejeződését találták (4), melyek szerepét a genetikai vizsgálatok során azonosított egy nukleotidos polimorfizmusok (SNP) is alátámasztottak (5). Ezek alapján jogos az igény a lehetőségeinkhez mért tisztánlátásra, valamint hogy azonosítsuk azokat a faktorokat, melyek a HSben szerepet játszanak akár arra specifikusan, akár pedig egy általános gyulladás részeként.…”
Section: Acne Inversa: Miért Nem Acne éS Nem Is Hidradenitis?unclassified